2012
DOI: 10.1158/1078-0432.ccr-11-2483
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Gene Expression Signature Model for Risk Stratification of Patients with Neuroblastoma

Abstract: Purpose Neuroblastoma is an embryonal tumor with contrasting clinical courses. Despite elaborate stratification strategies, precise clinical risk assessment still remains a challenge. The purpose of this study was to develop a PCR-based predictor model to improve clinical risk assessment of patients with neuroblastoma. Experimental Design The model was developed using real-time PCR gene expression data from 96 samples and tested on separate expression data sets obtained from real-time PCR and microarray stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 31 publications
0
69
0
Order By: Relevance
“…21 NDPK-A OR NDPK-A S120G ENHANCES NEUROBLASTOMA CELL INVASIVENESS Metastasis-associated cellular processes include decreased cell adhesion as well as increased cell survival, migration, invasion, and colonization. For simplicity here, these cellular processes are collectively termed cell invasiveness.…”
Section: Nm23-h1 Genetics and Prognosis Of Neuroblastomamentioning
confidence: 99%
“…21 NDPK-A OR NDPK-A S120G ENHANCES NEUROBLASTOMA CELL INVASIVENESS Metastasis-associated cellular processes include decreased cell adhesion as well as increased cell survival, migration, invasion, and colonization. For simplicity here, these cellular processes are collectively termed cell invasiveness.…”
Section: Nm23-h1 Genetics and Prognosis Of Neuroblastomamentioning
confidence: 99%
“…Neuroblastoma risk assessment was defined by the International Neuroblastoma Staging System (INSS) [30]. Patients' clinical and biological characteristics are displayed in Supplementary Table 1 [31][32][33].…”
Section: Patients Samples and Cell Linesmentioning
confidence: 99%
“…In neuroblastoma, all studies reported an enhanced expression of NME1 in tumors, correlated, when evaluated, with a poor prognosis (Hailat et al, 1991;Leone et al, 1993b;Chang et al, 1994;Hiyama et al, 2004;Garcia et al, 2012). In accordance with a metastatic promoting role, enhanced NME1 expression in the NB69 neuroblastoma cell line increased cell migration and metastatic potential (Almgren et al, 2004).…”
Section: Notementioning
confidence: 98%
“…This was observed with cell lines derived from melanoma (Leone et al, 1991) and from breast (Leone et al, 1993a), colon (Suzuki et al, 2004), lung (Nie et al, 2008), liver (She et al, 2010), ovarian (Li et al, 2006), prostate (Andolfo et al, 2011) and oral (Wang YF et al, 2008) carcinomas. In other types of cancers such as neuroblastoma (Leone et al, 1993b;Garcia et al, 2012), hematopoietic malignancies (Yokoyama et al, 1998) and osteosarcoma (Liao et al, 2000), a high tumoral expression was noted which was most often correlated with poor clinical outcome.…”
Section: Homologymentioning
confidence: 99%